Improving the Quality of Outpatient Diabetes Care Using an Information Management System: Results From the Observational VISION Study. (January 2016) - Weissmann, Joerg; Mueller, Angelika; Messinger, Diethelm; Parkin, Christopher G.; Amann-Zalan, Ildiko
Background: This study aimed to evaluate the effects of information management system (IMS) use with individuals with type 1 and type 2 diabetes who were treated in outpatient settings. Methods: In this 7-month, prospective, observational study, 965 adults with diabetes, mean (SD) baseline HbA1c 8.61(1.2)% (70.6[13.1] mmol/mol), were recruited from 132 outpatient care centers in Germany and Denmark. HbA1c was measured at baseline, month 4, and month 7. IMS reports were generated from uploaded self-monitored blood glucose data and therapy adjustments were documented at months 1 and 4. Hypoglycemic events were documented. Results: Mean (SD) HbA1c decreased from baseline in type 1 and type 2 diabetes patients at month 4 (–0.61[1.03]% (–6.7[11.3] mmol/mol), n = 213; –0.88[1.22]% (–9.6[13.3] mmol/mol), n = 589, respectively) and month 7 (–0.64[1.02]% (–7.0[11.1] mmol/mol), n = 219; –0.93[1.27]% (–10.2[13.9] mmol/mol), n = 594, respectively), all P < .0001, with no increase in hypoglycemic events. Therapy was adjusted in 106(42.7)% type 1 and 349(52.4)% type 2 diabetes patients at months 1 and 105(42.3)% type 1 and 282(42.3)% type 2 diabetes patients at month 4. Physicians used IMS reports to make therapy adjustments in 90% of patients at month 1 and 86% of patients at month 4. Conclusions: Integration of the IMS into outpatient care facilitates significant improvements in glycemic control.